Gender differences in clinical profile and risk factors for obstructive sleep apnea in a public health care setting - Kapse, Vijay; Patel, Vikas; Mhaisekar, Dilip; Kulkarni, Mithilesh (International Journal of Research in Medical Sciences, 2019)
Background: Obstructive Sleep Apnea Syndrome is an increasingly prevalent chronic condition which is, unfortunately, still underdiagnosed. It is peculiarity of this noisy disease that it announces itself to everyone within earshot-except its victims. The intermittent hypoxemia and sleep fragmentation caused by recurrent episodes of upper airway collapse are chiefly responsible for the pathophysiology associated with this condition. Methods: The present study was carried out from January 2014 to August 2015 in a tertiary care government hospital. In this comparative hospital based study 94 patients with Sleep Disordered Breathing and >13 years of age were included. There were 58 males and 36 females in the present study. All patients who satisfied inclusion criteria were studied after taking written consent. Collection of data was carried out with predesigned proforma. Results: Of all the 94 patients who underwent overnight Polysomnographic study,80 patients were diagnosed as Obstructive Sleep Apnea. Risk factor of OSA have gender differences in their distribution. Female patient is older with significantly higher mean age compared to male patients with OSA (52.9 vs 44.7 years). Females are having significantly higher BMI compared to male OSA(38.2 vs 31.5) but neck circumference is higher in males (44.7 Vs 38.1 cm).The prevalence of Smoking and Alcoholism as a risk factor is higher in male patients while endocrine disorder are more common in females. ENT abnormalities are present more or less equally in both the sexes. Conclusions: In the present study females’ patients with Obstructive Sleep Apnea were mainly Older, Obese, Postmenopausal and endocrine disorder like Hypothyroidism were more prevalent while male patients were Smoker, Alcoholic and had higher neck circumference.